DAMPAK PERCERAIAN ORANG TUA TERHADAP ANAK (Studi Kasus Di SMA Negeri 1 Kecamatan Nosu Kabupaten Mamasa) - Ahmad Al Yakin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2014)
This research is motivated by the phenomenon of divorce and separation of parents were influential for the formation of children's behavior and personality. The purpose of this study was to determine the impact of parental divorce on children in public SMA 1 nosu districts nosu Mamasa district. This type of research is qualitative descriptive. The subject of this research, students of class XI IPA who have parents with backgrounds have divorced. Based on the recommendation of the supervising teacher that netted two students, such as Mega and Rismawati Rena. Methods of data collection using interviews and observation. Based on the results of research in public SMA 1 nosu districts nosu district Mamasa known that children of divorce indicates that the situation of children who come from families who had just divorced, usually have an impact on the issue of emotion expressed by not being able to manage his emotions well, be it emotional angry or sad, often aloof and withdrawn. But not all children of divorce experienced something like that, for the subject who has found her identity in line with the development of psychological, physical, and psychosocial well so that they can react to frustration caused by family problems with a positive attitude.